Pelatihan Remaja Anti Klitih pada Siswa SMP Muhammadiyah 2 Kalasan Sleman Daerah Istimewa Yogyakarta - Purwadi, Purwadi; Supriyanto, Agus; Saputra, Wahyu Nanda Eka (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
The purpose of this activity is to provide assistance and training for students in SMP Muhammadiyah 2 Kalasan in Special Region of Yogyakarta to have a commitment not to show one of the aggression behaviors in Yogyakarta which is often called klitih. One form of this behavior is that teenagers injure another teenager intentionally and without reason (done randomly to the victim) by injuring the victim with various tools when the victim is riding a motorcycle. The method used in this activity was training and mentoring for students of SMP Muhammadiyah 2 Kalasan. The product of this activity is the emergence of a community in a school that is engaged in providing counseling and support for friends who are having problems and who are at risk of being involved in making a klitih behavior.